Desain Baterai Lithium-Ion Pengaruh Iradian Dan Temperatur Menggunakan PV Syst and Meteonorm Software - Izzatul Umami; Intan Sekar Novitasari; Hidayatul Nurohmah; Dwi Ajatmo; Ali, Machrus (Elconika: Jurnal Teknik Elektro, 2024)
Indonesia is a country with significant potential for developing solar energy. However, one of the challenges in the electricity sector is the reliance on fossil fuels as the primary energy source. To mitigate the impact of this dependence on fossil fuels, it is crucial to explore new sources of renewable electricity. Solar cells, which convert sunlight or ultraviolet (UV) rays into electrical current, offer a promising solution. Sunlight is a sustainable and abundant energy source, making it a viable option for future energy production. Due to the nature of solar cells, which depend on sunlight, the output they produce is variable and influenced by changing weather conditions. Therefore, energy storage solutions, such as lithium-ion batteries, are needed to store the electricity generated by solar cells. This study will examine the characteristics and efficiency of solar cell input on the capacity of lithium-ion battery storage systems, focusing on the relationship between sunlight intensity and the generated current and voltage. An off-grid photovoltaic (PV) system relies solely on solar energy, utilizing a series of photovoltaic modules. Consequently, sunlight intensity significantly impacts the solar cell's performance by affecting the voltage and current produced, which in turn influences the system's performance. This research aims to assess the efficiency, advantages, and disadvantages of comparing the output results between series and parallel configurations of solar cells to meet desired needs. Testing and data collection will be conducted using simulations with PV Syst and Meteonorm software.